Misbehaving at the crossroads : essays & writings - Jeffers, Honorée Fanonne, 1967- (Harper, an imprint of HarperCollins Publishers, 2025)
Honorée Fanonne Jeffers is at a crossroads. Traditional African/Black American cultures present the crossroads as a place of simultaneous difficulty and possibility. In contemporary times, Kimberlé Crenshaw coined the phrase "intersectionality" to explain the unique position of Black women in America. In many ways, they are at a third crossroads: attempting to fit into notions of femininity and respectability primarily assigned to White women, while inventing improvisational strategies to combat oppression. In Misbehaving at the Crossroads, Jeffers explores the emotional and historical tensions in Black women's public lives and her own private life. She charts voyages of Black girlhood to womanhood and the currents buffeting these journeys, including the difficulties of racially gendered oppression, the challenges of documenting Black women's ancestry; the adultification of Black girls; the irony of Black female respectability politics; the origins of Womanism/Black feminism; and resistance to White supremacy and patriarchy. As Jeffers shows with empathy and wisdom, naming difficult historical truths represents both Blues and transcendence, a crossroads that speaks.